Penerapan Program Bahasa Arab-Inggris di Pondok Pesantren Al-Qur’an Nurul Ulum Kretek Bantul - Hadi Muhtarom (IIQ An Nur Yogyakarta, 2023)
This research aimed to analyze one of the programs as an innovation from Al-Quran Islamic Boarding School of Nurul Ulum Kretek Bantul. The program was a language program, namely Arabic and English. The method used in this research was a qualitative method. The sources used as reference for analysis were divided into two, namely primary sources and secondary sources. The language program at Al-Quran Islamic Boarding School of Nurul Ulum Kretek Bantul was an important program to carry out. Both Arabic and English had their own urgency for students who were also santri. Both in the field of education and in the field of work. In the ongoing process of this language development program, there were still shortcomings so further evaluation as needed. The problems faced by the Al-Quran Islamic Boarding School of Nurul Ulum Kretek Bantul in this development program included the lack of expert teaching staff in the field of language and the absence of special learning modules at each grade level.